(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The purpose of this study was to examine the equipment used in five hospitals located in Jigawa state. Finding Methicillin-Resistant Staphylococcus aureus (MRSA) on hospital equipment in a few Dutse metropolitan hospitals was the main goal. Three hundred and fifty hospital instruments in all were swabbed and then examined. Tests for antibiotic susceptibility were conducted after S. aureus was isolated and identified. The isolates were most effectively treated by gentamicin and ciprofloxacin, according to the results. Primary healthcare facilities contained 31 S. aureus isolates and 16.67% MRSA isolates, whereas secondary healthcare hospitals had 48 S. aureus isolates and 55.56% MRSA isolates. There were 25 S. aureus isolates and 27.78% MRSA isolates from tertiary healthcare facilities. The mecA and blaZ genes’ polymerase chain reaction (PCR) analyses revealed amplicons of 336 bp and 400 bp, respectively, which were in line with control samples. Six of the 11 isolates that were tested tested positive for mecA, suggesting resistance to methicillin, and nine tested positive for blaZ, indicating the synthesis of B-lactamase. In conclusion, patients, medical staff, and the general public are seriously threatened by the MRSA infection that exists in these facilities.